(8x^2+5x+3)+(-5x^6-2x^5+4x^2-2x)=
8x^2+5x+3-5x^6-2x^5+4x^2-2x=
-5x^6-2x^5+(8-4)x^2+(5-2)x+3=
-5x^6-2x^5+4x^2+3x+3
Answer: Option B. -5x^6-2x^5+4x^2+3x+3
Multiply by a across the formula
Hi Jessica,
<span>Remember PEMDAS (Parenthesis, Exponents, Multiplication & Division, Addition & Subtraction).
√3 x 66.15/4.41 {Exponents/Cube & Square Roots First}
1.73 x 66.15 ÷ 4.41 {Multiplication}
114.4395 ÷ 4.41 {Division}
25.95 {Final Answer}
Cheers,
Izzy</span>
Answer:
Step-by-step explanation:
perp. -1/2
y + 3 = -1/2(x - 3)
y + 6/2 = -1/2x + 3/2
y = -1/2x - 3/2
Answer:
If it's an addition problem then just add 3 cups
Step-by-step explanation:
There isn't too much context here buddy :p